La peur dans l’œuvre d’Erckmann-Chatrian : du folklore au fantastique - Benhamou, Noëlle (Romanica Silesiana)
Two inhabitants of Lorraine, named Emile Erckmann (1822–1899) and Alexandre Chatrian (1826–1890) – authors of numerous short stories inspired from local and Rhineland’s folklore – wrote fantastic stories in which fear and anxiety are given pride of place. All the ingredients of fear are present – ghosts, apparitions, magnetism, lycanthropia, murders, violent deaths, miscarriages of justice. Would this subtle mixture of folklore and fantastic have a didactic, even metaphysical aim? Key words : fear, fantastic, ghost, short story, didactics, metaphysics